2007
DOI: 10.1063/1.2771661
|View full text |Cite
|
Sign up to set email alerts
|

Coherent vortices in high resolution direct numerical simulation of homogeneous isotropic turbulence: A wavelet viewpoint

Abstract: Coherent vortices are extracted from data obtained by direct numerical simulation ͑DNS͒ of three-dimensional homogeneous isotropic turbulence performed for different Taylor microscale Reynolds numbers, ranging from Re = 167 to 732, in order to study their role with respect to the flow intermittency. The wavelet-based extraction method assumes that coherent vortices are what remains after denoising, without requiring any template of their shape. Hypotheses are only made on the noise that, as the simplest guess,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
95
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 82 publications
(102 citation statements)
references
References 30 publications
7
95
0
Order By: Relevance
“…Excluding these regions would cut the spectrum up to k ∼ l −1 , and the scales are easy to separate. An evidence for this second approach comes from the numerical simulations [12]: the observed 'coherent structures' with high vorticity, i.e. vortex filaments, are found to be very stable, the lifetime exceeding many times the largest-eddy turnover time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Excluding these regions would cut the spectrum up to k ∼ l −1 , and the scales are easy to separate. An evidence for this second approach comes from the numerical simulations [12]: the observed 'coherent structures' with high vorticity, i.e. vortex filaments, are found to be very stable, the lifetime exceeding many times the largest-eddy turnover time.…”
Section: Discussionmentioning
confidence: 99%
“…This contradicts to the idea of cascade. In [12] it is shown that these smallscale structures are responsible for the 5/3 law. Picking them out breaks the power-law energy spectrum in the whole inertial range.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cao (1997), Wu and Yang (2004), Wu and Jiang (2007)). Considerable recent work therefore focusses on the structural form of these features of flow, their role in fluid and sediment entrainment, bed shear stress generation, energy transfer and velocity asymmetry; and the influence of the space-time structure of the flow, with emphasis on oscillatory flows, and different bed roughnesses (Adrian and Marusic, 2012;Carstensen et al, 2010;Carstensen et al (2012); Grigoriadis et al, 2013;Hardy et al, 2010;Hare et al, 2014;Okamoto et al, 2007). Advanced visualisation and data analysis techniques reveal complex interactions between passing coherent energetic structures and sediments in suspension, such as particle response to turbulent fluctuations in the frequency domain (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The assessment of adaptive CVS for turbulent flows bounded by walls of complex geometries is also an important issue. In [24], it was shown that wavelet representations are more efficient than non-adaptive representations for isotropic turbulent flow, as the Reynolds number increases. It is thus expected that adaptive CVS is an attractive tool for high Reynolds number flows bounded by walls in complex geometries.…”
Section: Discussionmentioning
confidence: 99%